1994
DOI: 10.1002/ijc.2910590610
|View full text |Cite
|
Sign up to set email alerts
|

Brain cancer incidence, mortality and case survival: Observations from two australian cancer registries

Abstract: Data from 2 Australian cancer registries covering a population of 1.7 million people were combined for the purposes of analysing brain cancer incidence, mortality and survival patterns for the time period 1978 through 1992. A total of 1,752 cases of primary brain cancer were registered, representing age-standardised incidence rates of 6.7 per 100,000 in men and 4.6 in women. Histological confirmation was available for 94% of cases. The incidence rate among persons aged 75 or over was higher during 1986-1992 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 18 publications
3
17
0
4
Order By: Relevance
“…Most previous studies (Mosso et al, 1992;Linet et al, 1999;Kaatsch et al, 2001;Gonzalez et al, 2004), but not all (Shugg et al, 1994) have found decreases in mortality from CNS tumours in childhood over the past three decades, probably owing to improved therapy. In the present study, however, we observed an annual 1.4% increase in mortality rate (younger children 1.8%; older children 1.3%), which indeed supports that the observed annual 2.9% increase in incidence rate (younger children: 3.7%; older children: 2.4%) is biologically true.…”
Section: Discussionmentioning
confidence: 92%
“…Most previous studies (Mosso et al, 1992;Linet et al, 1999;Kaatsch et al, 2001;Gonzalez et al, 2004), but not all (Shugg et al, 1994) have found decreases in mortality from CNS tumours in childhood over the past three decades, probably owing to improved therapy. In the present study, however, we observed an annual 1.4% increase in mortality rate (younger children 1.8%; older children 1.3%), which indeed supports that the observed annual 2.9% increase in incidence rate (younger children: 3.7%; older children: 2.4%) is biologically true.…”
Section: Discussionmentioning
confidence: 92%
“…The international literature on overall brain cancer survival comes from a large number of regions: Europe, the UK, the Nordic countries, Australia, the US and Korea, and tends to be consistent in reporting improved survival rates beginning in the 1970s [3][4][5][6][7][8] through to the present. 19 In Canada, an improvement in survival rates for brain cancer patients between 1967 and 1986 was reported in the province of Saskatchewan which was attributed to patients under the age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is not well recognized by the general population that there is wide variation in the prognosis of patients with brain cancers, depending on the tumour histology type, patient and clinical features, all of which may influence diagnosis and treatment. Based on information from many other countries, [3][4][5][6][7] it is well established that early age at diagnosis is associated with better prognosis for patients with these tumours, largely because the histology types that occur most frequently in younger age groups have a less aggressive nature. Mao 8 demonstrated an improvement in brain cancer survival rates in the Canadian province of Saskatchewan between 1967 and 1986 that was primarily due to survival improvement in patients under the age of 65.…”
mentioning
confidence: 99%
“…In most industrialized countries, recent studies have demonstrated an increase in incidence rates over time, particularly for glial tumors in subjects aged over 60 years [6][7][8][9][10]. This may be due to better diagnostic techniques and easier access to care, but this increase might also be linked to changes in risk factors of an environmental, professional or individual nature [11].…”
Section: Introductionmentioning
confidence: 99%